The Impact of Social Media on the Psyche of Youth: A Factorial Analysis - Zahoor, Rubina (Journal of Science & Technology, 2023)
Netizens have adopted a wide range of digital technologies into their communication realms. Ambiguity construes a notion, of relying on multiple platforms for communication instead of swapping one medium for another. In retrospect, this anomaly strikes curiosity amongst researchers: Which introspect does each of these media fulfil? Hitherto, our article conducts comparative work that examines the ramifications obtained from Facebook with those from Instagram. This comparison between social media platforms aggregates conclusions about multiple social media acolytes and the tug-of-war between need and want. Data were collected from UAE high school students, based in Dubai, through a multimethod study based on 51 surveys. A factorial analysis of desire-based notions obtained from Facebook revealed six key dimensions: pastime, affection, fashion, information, sociability, and procuring friends of the opposite gender. Comparative analysis showed that Facebook is about having fun and knowing about the social activities occurring in one’s social network, whereas Instagram is geared toward the synopsis of reason. The researcher discusses differences between the two applications and outlines a framework based on application and slaking theory concerning youth integration in social media.